De-/Re-constructing Model Transformation Languages - Syriani, Eugene; Vangheluwe, Hans (Electronic Communications of the EASST, 2010)
The diversity of today’s model transformation languages makes it hard to compare their expressiveness and provide a framework for interoperability. De-constructing and then re-constructing model transformation languages by means of a unique set of most primitive constructs facilitates both. We thus introduce T-Core, a collection of primitives for model transformation. Combining T-Core with a (programming or modelling) language enables the design of model transformation formalisms. We show how basic and more advanced features from existing model transformation languages can be re-constructed using T-Core primitives.